Supplemental feed for calves prior to weaning - Woolfolk, J.S.; Conway, K.; Schalles, R.R.; Smith, E.F. (Kansas State University. Agricultural Experiment Station, 2011)
A mixture of 60% dehydrated alfalfa crumbles and 40% dry rolled sorghum grain was fed ad lib to calves 30 days before weaning. The calves ate an average of 2.6 lbs. per day and gained 0.32 lbs more per day average during the 30 days than calves receiving no supplemental feed. During the next 30 days all calves received the ration ad lib. Calves continuing on the ration gained 0.48 lbs. more per day average than those that had received no supplement before weaning.
Keywords: Beef; Weaning; Alfalfa; Sorghum grain